The dependence of aluminum nitride yield on weight mass and air pressure at aluminum nanopowder combustion - L. O. Root; E. S. Zvyagintseva; A. P. Ilyin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The authors have proved by the experiment the methods for increasing aluminum nitride yield in air combustion products of aluminum nanopowder: the increase of mass of aluminum nanopowder weight and air pressure rise. It was ascertained that increasing the mass of combusted aluminum nanopowder weight to 15 g or rising air pressure to 120 kPa it is possible to increase aluminum nitride yield approximately by 30 %. The earlier proposed mechanism of forming whiskers from gas phase was proved by the experiments.